Expression of kinase-dependent glucose uptake in Saccharomyces cerevisiae. - Bisson, L F (1984)
There are both low- and high-affinity mechanisms for uptake of glucose in Saccharomyces cerevisiae; high-affinity uptake somehow depends on the presence of hexose kinases (L. F. Bisson and D. G. Fraenkel, Proc. Natl. Acad. Sci. U.S.A. 80:1730-1734, 1983; L. F. Bisson and D. G. Fraenkel, J. Bacteriol. 155:995-1000, 1983). We report here on the effect of culture conditions on the level of high-affinity uptake. The high-affinity component was low during growth in high concentrations of glucose (100 mM), increased as glucose was exhausted from the medium, and decreased again during prolonged incubation in the stationary phase. The higher level of uptake was found in growth on low concentrations of glucose (0.5 mM) and in growth on normal concentrations of galactose, lactate plus glycerol, or ethanol. These results suggest that some component of high-affinity uptake is repressible by glucose. A shift from medium with 100 mM glucose to medium with 5 mM glucose resulted in up to a 10-fold increase in the level of high-affinity uptake within 90 min; the increase did not occur in the presence of cycloheximide or 2,4-dinitrophenol or in buffer alone with low glucose, suggesting that protein synthesis or energy metabolism (or both) was required. Reimposition of the high glucose concentration caused loss of high-affinity uptake, a process not prevented by cycloheximide. The use of hexokinase single-gene mutants showed that the derepression of high-affinity uptake was not clearly correlated with changes in levels of the kinases themselves. These results place the phenomenon of high- and low-affinity uptake in a physiological context, in that high-affinity uptake seems to be expressed best in conditions where it might be needed. Apparent similarities between glucose uptake in yeast and animal cells are noted.